1970
DOI: 10.3329/jcmcta.v19i2.3872
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of ABO and Rh(D) blood group among leprosy patients

Abstract: Key words: ABO blood group, Rh(D) blood group; leprosydoi: 10.3329/jcmcta.v19i2.3872Journal of Chittagong Medical College Teachers' Association 2008: 19(2):51-53

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…For instance, a study in China on 459 Chinese leprosy patients and 15 261 healthy individuals found non-significant difference between leprosy patients and healthy controls [22]. In the same way, studies conducted in Bangladesh and India [23,24] are also consistent with the present study. Furthermore, the analysis of combined data of 27 series from 14 different countries among 11 261 leprosy patients and 390 602 healthy controls brought similar conclusion [25].…”
Section: Abo Blood Groupsupporting
confidence: 80%
“…For instance, a study in China on 459 Chinese leprosy patients and 15 261 healthy individuals found non-significant difference between leprosy patients and healthy controls [22]. In the same way, studies conducted in Bangladesh and India [23,24] are also consistent with the present study. Furthermore, the analysis of combined data of 27 series from 14 different countries among 11 261 leprosy patients and 390 602 healthy controls brought similar conclusion [25].…”
Section: Abo Blood Groupsupporting
confidence: 80%
“…It varies from race to race, one country to another and even in different regions of a country. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This spectrum of difference may be attributed to genetic factors and natural selection which is affected mainly by traditions and habits namely exogamy and endogamy. Global frequency pattern of the type B blood allele is highest in central Asia and in few pockets of Africa but lowest in the America and Australia.…”
Section: Introductionmentioning
confidence: 99%